Mixed‐Metal MOF‐74 Templated Catalysts for Efficient Carbon Dioxide Capture and Methanation. (4th December 2020) - Zurrer, Timothy; Wong, Kenneth; Horlyck, Jonathan; Lovell, Emma C.; Wright, Joshua; Bedford, Nicholas M.; Han, Zhaojun; Liang, Kang; Scott, Jason; Amal, Rose
Abstract: The vast chemical and structural tunability of metal–organic frameworks (MOFs) are beginning to be harnessed as functional supports for catalytic nanoparticles spanning a range of applications. However, a lack of straightforward methods for producing nanoparticle‐encapsulated MOFs as efficient heterogeneous catalysts limits their usage. Herein, a mixed‐metal MOF, NiMg‐MOF‐74, is utilized as a template to disperse small Ni nanoclusters throughout the parent MOF. By exploiting the difference in NiO and MgO coordination bond strength, Ni 2+ is selectively reduced to form highly dispersed Ni nanoclusters constrained by the parent MOF pore diameter, while Mg 2+ remains coordinated in the framework. By varying the ratio of Ni to Mg in the parent MOF, accessible surface area and crystallinity can be tuned upon thermal treatment, influencing CO2 adsorption capacity and hydrogenation selectivity. The resulting Ni nanoclusters prove to be an active catalyst for CO2 methanation and are examined using extended X‐ray absorption fine structure and X‐ray photoelectron spectroscopy. By preserving a segment of the Mg 2+ ‐containing MOF framework, the composite system retains a portion of its CO2 adsorption capacity while continuing to deliver catalytic activity. The approach is thus critical for designing materials that can bridge the gap between carbon capture and CO2 utilization. Abstract : The thermal treatment of mixed‐metal metal–organic frameworks (MOFs) is harnessed to bridge the gap between direct air capture and CO2 methanation with one material. Ni 2+ is selectively reduced within the MOF to form highly dispersed Ni nanoclusters active for CO2 hydrogenation. Over 70% of the CO2 adsorption capacity is preserved for the best‐performing catalysts, highlighting the dual functionality of the nanoparticle‐MOF structure.